Hubungan Kerasionalan Obat Antihipertensi Dengan Kontrol Tekanan Darah Pada Pasien Stroke Non-Hemoragik di Instalasi Rawat Inap RS X Surakarta Tahun 2024 - Locita , Zana Sahya; Mutmainah, Nurul (Journal of Pharmaceutical and Sciences, 2025)
Background: Non-hemorrhagic stroke or ischemic stroke is the most common type of stroke and remains one of the leading causes of mortality and long-term disability. Blood pressure management through antihypertensive therapy is a key component of secondary prevention; however, variations in clinical practice indicate that the rational use of these medications still requires evaluation. Objective: This study aims to determine the relationship between the rationality of antihypertensive therapy and blood pressure control in non-hemorrhagic stroke patients based on clinical parameters in the inpatient ward of Hospital X, Surakarta. Methods: This research employed an analytical observational design with a retrospective cross-sectional approach. Data on antihypertensive use were collected from medical records of patients hospitalized in 2024, and a total of 100 patients met the inclusion criteria. Data analysis was performed using the Chi-square test. Results: Among non-hemorrhagic stroke patients in the inpatient ward of Hospital X Surakarta in 2024, 90 patients received rational antihypertensive therapy. Antihypertensive treatment was predominantly from the dihydropyridine CCB class, particularly amlodipine, either as monotherapy or in combination. Fisher’s exact test analysis showed a p-value < 0.05, indicating a significant association between the rationality of antihypertensive therapy and blood pressure control. Conclusion: There is a significant relationship between the rationality of antihypertensive therapy and blood pressure control in non-hemorrhagic stroke patients, highlighting the importance of rational drug selection as a crucial aspect of secondary prevention strategies.